Diabetes Mellitus And Posterior Subcapsular Type Of Senile Cataract In Pre-Surgery Patients At PHC Hospital Surabaya - Vania, Aline; Ernawati, Titiek; Steven, Steven (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction: A cataract is an opacity of the lens, caused by many factors. Rapid Assessment of Avoidable Blindness (RAAB) that has been conducted in three provinces (NTB, Jawa Barat, dan Sulawesi Selatan) in 2013-2014 has come into a prediction of new cases of cataract blindness will increase 0.1% from the population or about 250.000 people a year. Metabolic disease such as Diabetes Mellitus (DM) is one of the well-known factors of cataract. Many studies, including Blue Mountains Eye Study and Beaver Dam Eye Study, have proved the increase of incidence and prevalence of posterior subcapsular cataract on diabetic patients. Posterior subcapsular cataract (PSC) means the lens opacity starts from the posterior part of the lens. Aim: to study whether there is a correlation between DM and PSC in Surabaya or not. Method: This research used the observational study with analytic design, and the method used in this research is cross-sectional. Spearman correlation was used in this research to test the correlation between variables. Result: The population of this study is all pre-surgery senile cataract patients on PHC Hospital Surabaya. Twenty-two samples meet the inclusion and exclusion criteria. The analytic result shows that the correlation between diabetes and the posterior subcapsular senile cataract is insignificant (p= -0.092). Conclusion: The exact pathogenesis of PSC remains unknown. It shows increased degenerative changes and the accumulation of extracellular material which can happen on diabetes patients. However, it has been noted to occur as a result of a gene mutation. That explained the insignificancy result of this research and the different distribution of PSC in the world. Descriptive research about cataract types epidemiology in Indonesia is needed.